2011
DOI: 10.1021/jo200096x
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Decarboxylative Coupling of Propiolic Acids: One-Pot Synthesis of 1,4-Disubstituted 1,3-Diynes via Sonogashira−Homocoupling Sequence

Abstract: One-pot synthesis of symmetric 1,4-disubstituted 1,3-diynes from iodoarenes and propiolic acid via Sonogashira reaction followed by Pd-catalyzed decarboxylative homocoupling is developed in high yields. Also, this system allows the one-pot synthesis of unsymmetric 1,4-disubstituted 1,3-diynes by cross-coupling of two different 3-substituted propiolic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 48 publications
0
40
0
Order By: Relevance
“…The preparation for this compound was according to a similar procedure described in the literature. 21 Synthesis of Compound 5. A solution of hexyl bromide (1.05 g, 6.36 mmol) in anhydrous acetone (5 mL) was added dropwise into a mixture of compound 6 (1.5 g, 6.41 mmol) and potassium carbonate (0.8 g, 5.8 mmol) in anhydrous acetone (15 mL) at 60°C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…The preparation for this compound was according to a similar procedure described in the literature. 21 Synthesis of Compound 5. A solution of hexyl bromide (1.05 g, 6.36 mmol) in anhydrous acetone (5 mL) was added dropwise into a mixture of compound 6 (1.5 g, 6.41 mmol) and potassium carbonate (0.8 g, 5.8 mmol) in anhydrous acetone (15 mL) at 60°C.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Although 1,4‐diarylbutadiyne is the key intermediate and can be obtained from the aryl iodide, the direct formation of desired product 4 from the aryl iodide failed. The previously reported conditions did not give the cyclized product 4 .…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, Park et al [114] reported a Pd-catalyzed decarboxylative coupling (see Chapter 3 for further details on decarboxylative coupling reactions) of propiolic acids, which involves a Sonogashira-Hagihara homocoupling sequence. Their reaction represents a new approach to the synthesis of 1,3-diynes, besides the classical approaches, which include Glaser coupling, Chodkiewicz-Cadiot coupling, Rossi's protocol, and Lei's protocol.…”
Section: Arylations With the Sonogashira-hagihara Reactionmentioning
confidence: 99%
“…Figure 1.33 The Sonogashira-Hagihara reaction variant of Fabrizi et al [113] with arenediazonium salts.Figure 1.34 The Pd-catalyzed decarboxylative coupling as described by Park et al[114].…”
mentioning
confidence: 99%